Women and adaptive capacity to climate change in East African seascapes – Zanzibar as an example - de la Torre-Castro, Maricela; Lindström, Lars; Jiddawi, Narriman S.; Pike, Felicity; Max, Astrid (Frontiers in Marine Science, 2022)
As the climate crisis persists, there is a crucial need to increase knowledge on adaptive capacity and the underlying factors building it. This is particularly important for disadvantaged groups, such as coastal women in East Africa. Women’s livelihoods in these seascapes are and will be more severely affected by climate change and the capacity of East African states to deal with these challenges is limited in terms of financial and human capital. In this research, we investigated the underlying factors building the adaptive capacity of coastal women in Zanzibar (Unguja Island), Tanzania. Coastal women (N=117) were interviewed in villages around the island to gather information about potential factors supporting adaptive capacity. This was analysed applying Cinner et al (2018) five domains typology for adaptive capacity, i.e. assets, flexibility, organizations, learning and agency. The results show that women had relatively low adaptive capacity, extended poverty and very high dependence on seaweed farming of red algae, a livelihood providing low income and already being seriously affected by climate variability and change. Women’s observations of key variables related to environmental changes corresponded to most scientific findings. It was, however, unclear how that knowledge is useful and enhances adaptive capacity. Adaptive capacity was generally low but individual differences were found in which ten women had a high income. The results show that the factors underlying adaptive capacity are complex and interact with each other, being positive, negative and unclear. Many of the identified factors deserve future research. This study adds to the pool of knowledge by addressing women (not only men); coastal ecosystems (as land and freshwater systems are more studied) and the individual level (since most studies focus on national and community levels). The study illustrates that institutional renewal, bridging and cooperation is possible in Zanzibar bringing good news to the region.